10 futures - Pryor, Michael (North Sydney, N.S.W. : Random House Australia, 2012)
"Sam and Tara. Best friends in a future when artificial intelligence organises our lives, and micropets are the latest craze."--Back cover.
For adolescents.
Also available online.
Keywords: Future -- Juvenile fiction; Earth (Planet) -- Juvenile fiction